Notes on stability of the generalized gamma functional equation - Gwang Hui Kim; Bing Xu; Weinian Zhang (International Journal of Mathematics and Mathematical Sciences)
The Hyers-Ulam stability in three senses is discussed by Kim (2001) for the generalized gamma functional equation g(x+p)=a(x)g(x) under some conditions which involve convergence of complicated series. In this note, those conditions are simplified to be checked easily and more interesting examples other than the classical gamma functional equation are displayed.